Administrative-Legal Regulation of the Implementation of Risk-Oriented Access in the Security Sector of Ukraine - K. L. Buhaichuk (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The publication provides a scientific analysis of the concept and characteristics of the category of “risk”, as well as the procedure for applying the concept of “risk management” in the activities of state authorities that are part of the system of subjects of the security and defense sector of Ukraine. An analysis of the state of administrative and legal regulation of issues related to the implementation of risk-oriented approaches in the activities of the Ministry of Defense of Ukraine, the Ministry of Internal Affairs of Ukraine and other subjects of the security and defense sector is carried out.